Note—An Interpretation of Fractional Objectives in Goal Programming as Related to Papers by Awerbuch, et al., and Hannan - Soyster, A. L.; Lev, B. (Management Science, 1978)
In this note we consider the validity of substituting a linear goal for a fractional goal in a mathematical program and provide a simple geometric interpretation that contrasts the essential differences between the two programs.